The Origin of the «General Part» of Brazilian Private Law - Schmidt, Jan Peter (2018)
The old Brazilian Civil Code from 1916, as well as the new one from 2002, began with a «General Part» in the spirit of the Pandektensystem. German legal doctrine, without further analysis, has often ascribed this characteristic to the influence of the German Civil Code (BGB). In Brazilian legal scholarship, on the other hand, the common view is quite different and holds that the idea of a «General Part» already existed in Brazil long before the BGB. However, a closer look reveals that both points of view are imprecise. While it is true that the «General Part» can be found in Brazilian private law already in the middle of the 19th century, it was no original creation, but based on the reception of German pandectist literature. At the same time, it needs to be emphasized that already in the Brazilian codification drafts from the 19th century, the «General Part» received, at least in parts, a treatment that differed from the German writings, and this independent tradition was continued up to the new Code from 2002. Hence, the idea of a «General Part» of private law is deeply entrenched in Brazilian legal culture, and the experiences with it are also of interest to the European observer.